PEMODELAN INVERSI DATA GEOLISTRIK 1-D UNTUK MENENTUKAN JENIS DAN KEDALAMAN BATUAN DASAR - Sudiar, Nofi Yendri; Akmam, Akmam (Sainstek : Jurnal Sains dan Teknologi, 2013)
Large earthquakes that occurred in the city of Padang had been expected to lead to changes in the structure of rocks beneath the surface composition including bedrock. Information about the composition of these rocks can be obtained by conducting geological surveys by using geoelectric methods (resistivity). This method is very good to know the condition or subsurface geological structures based on variations in resistivity. Research is inversion modeling. Equation used is forward modeling of resistivity 1-D using Jacobi matrix element finite difference approach. The data used are secondary data obtained from a previous study by the Department of Physics geoelectric exploration team of UNP. Resistivity is determined from an apparent resistivity measurements. Types are resistivity investigation using Vertical Electrical Sounding (VES) or depth investigation, with distinction anisotropic cross section in the vertical direction. The data inversion modeling results resistivity 1-D using IPI2WIN software obtained bedrock on the track of FE to FIS at the point of sounding 2/7 at depths >  18.3 m  the resistivity is 1002 Wm, on track of UNP gate to FT at the point of sounding 2/7 at depths >  25.6 m the resistivity is 744   Wm and at the point of sounding 5/7 on the surface to a depth of 3.75 m the resistivity is  778  Wm and on track of Balai Bahasa to Al Azhar mosque at the point of sounding 7/7 at a depth of >  11.4 m the resistivity is 923 Wm. While on the track of FIK to Lab. Biology is not found bedrock. Bedrock types found are suspected Andesite which form the basis for the layer above it as Alluvium and Sands, Sandstones and Clays. Modeling results are not so good, as evidenced by the error (RMS error) more than 5%, which means the calculation data does not approach the observations data. This is due to the amount of noise during measurement that sourced from the equipment used and the environmental conditions such as there are many trees, electrical wires and the route is paved.Key words: resistivity method, modeling, inversion, VES